Caracterização e aplicação da Blenda PEDOT : PSS/PVA na construção de eletrodos transparentes e dispositivos eletroluminescentes - Carr, Olivia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Since the discovery of the electronic properties of synthetic organic polymeric materials, several studies have been made to develop electronic and opto-electronics devices such as field effect transistors, light emitting diodes, light emitting electrochemical cells, solar cells and sensors. The motivation for this research was some specific features of organic materials such as flexibility, ultra-thin thickness, low cost and easy processing for application as transparent electrode in organic devices. This work aimed to study and characterize the polymer blend formed by the conductive polymer poly (3,4-ethylenedioxythiophene): poly (estirenosulfonado) (PEDOT:PSS) and the insulating polymer poly (vinyl alcohol) (PVA). The samples were characterized by spectroscopic techniques (UV-Vis), morphological (AFM) and electrical measurements AC and DC. The blend (PEDOT:PSS/PVA) containing (40/60), respectively, resulted in a percolated material, wherein the conductivity increases linearly with the concentration of conductive polymer. The results showed that the charge transport in the blends can be well described by the Variable Range Hopping (VRH-3D) model. Samples with concentrations below 10% by weight of PEDOT:PSS in the blend showed phase separation of the constituent polymers, resulting in two distinct electrical conduction processes, a predominant via the insulating matrix (PVA) and a second via islands formed by the polymer conductor (PEDOT:PSS). Optical characterization of the blend, for applications as transparent electrode, reveals that high electrical conductivity and low coefficient of optical absorption is obtained for concentrations close to 30% of PEDOT:PSS. The composition of the blend (PEDOT:PSS/PVA) with micro particles of Zn2SiO4:Mn, results in light emitting devices with emission peak at 530 nm and color purity of 88%

Desde a descoberta das propriedades eletrônicas de materiais poliméricos orgânicos sintéticos, várias pesquisas foram feitas a fim de desenvolver dispositivos eletrônicos e optoeletrônicos, como transistores de efeito de campo, diodos emissores de luz, células eletroquímicas emissoras de luz, células solares e sensores. A motivação para essas pesquisas tem sido algumas características específicas dos materiais orgânicos como a flexibilidade, dispositivos de espessura ultra-finos, baixo custo e fácil processamento. Este trabalho teve como objetivo estudar e caracterizar a blenda polimérica formada pelo polímero condutor Poli(3,4-etilenodioxitiofeno):Poli(estirenosulfonado) (PEDOT:PSS) e o polímero isolante Poli(álcool vinílico) (PVA). As amostras foram caracterizadas por técnicas espectroscópicas (UV-Vis), morfológicas (AFM) e medidas elétricas AC e DC. A blenda (PEDOT:PSS/PVA) composta por (40/60), respectivamente, apresentou um material percolado, na qual a condutividade cresce linearmente com a concentração do polímero condutor. Os resultados mostraram que o transporte de carga nas blendas pode ser bem descrito pelo modelo Variable Range Hopping (VRH-3D). Amostras com concentrações inferiores a 10% em massa de PEDOT:PSS na blenda apresentaram separação de fase entre os polímeros constituintes, levando a dois processos de condução elétrica distintos, um predominante através da matriz isolante (PVA) e outro através de ilhas constituídas pelo polímero condutor (PEDOT:PSS). Da caracterização óptica da blenda, para aplicações como eletrodo transparente, obteve-se filmes com alta condutividade elétrica e baixo coeficiente de absorção óptico, para concentrações próximas a 30% de PEDOT:PSS. A composição da blenda (PEDOT:PSS/PVA) com as micro partículas de Zn2SiO4:Mn, para aplicação em dispositivos EL, resultou em dispositivos emissores de luz com pico de emissão em 530 nm e pureza de cor de 88%
Keywords: Physics; Fisica; Eletrodos; Eletroluminescencia; Polimeros condutores; Percolação